PENGARUH PENDAPATAN PER KAPITA, ECONOMIC GROWTH RATE, ECONOMIC STRUCTURE, DAN TAX RATE TERHADAP TAX RATIO PADA NEGARA-NEGARA OECD DAN INDONESIA - Danny Wibowo (Universitas Jember, 2013)
The purpose of this study to identify and obtain evidence about the influence perkpita income, economic growth rate, economic structure, and the tax rate of the tax ratio in the OECD countries and Indonesia. Type of research is the use of quantitative data, the research is based on the measurement results in the form of numerical data. Sources used in research is secondary data. Methods of data collection in this study is to collect data by the method of documentation. The sampling technique used in this study was purposive sampling, the sampling technique with specific considerations. Because of the limitations of the data of the whole country, then the sample is taken the countries belonging to the OECD, including Indonesia. Based on statistical tests were performed, the results obtained are in the classical assumption test it can be concluded that the regression model has qualified the assumptions of normality, free from the problem of multicollinearity, heteroscedasticity, auto correlation. The overall effect of independent variables on the dependent variable is affected by 49.8%. Based on partial test or t test, indicated that of the four independent variables only the economic structure that significantly affect the tax ratio. Keywords: income capita, economic growth rate, economic structure, tax rate, tax ratio